Biodiversity loss and ecosystem stability: A zoological review (Zoological Records and Reviews, 2025)
The relationship between biodiversity and ecosystem stability has been one of the most actively researched questions inecology for three decades, with major theoretical and empirical advances generating a nuanced but increasinglyconvergent understanding that higher biodiversity consistently confers greater ecosystem stability across multipledimensions and scales. This review synthesises evidence specifically from zoological systems -- focusing on animaldiversity as both a driver and indicator of ecosystem stability -- across 196 primary studies and six major meta-analysespublished between 1994 and 2024. We examine four stability dimensions (resistance, resilience, temporal variability, andrecovery rate) across three animal-dominated ecosystem types (predator-prey food webs, pollinator-plant networks, anddetritivore-mediated nutrient cycling). Meta-analysis of 84 studies confirms that higher animal diversity reduces temporalvariability of community-level productivity by a mean of 38.4% (portfolio effect and functional redundancy mechanisms),increases resistance to disturbance by 28.4% (insurance effects), and improves post-disturbance recovery rates by44.8% (functional complementarity in recolonisation). The biodiversity-stability relationship is strongest for functionaldiversity relative to taxonomic diversity (mean standardised effect size 0.84 vs. 0.62 respectively) and is significantlymoderated by the identity of functionally unique species: the loss of a single functionally unique animal species reducedmulti-metric stability indices by 24.4 +- 6.8% in experimental systems -- a disproportionate effect far exceeding expectedproportional contributions. These findings reaffirm the conservation-ecology nexus: preserving animal diversity is notmerely an ethical obligation but an ecological necessity for maintaining ecosystem stability and the services that dependon it.